End moraines and ice marginal processes of surge-type glaciers. Brúarjökull and Eyjabakkajökull, Iceland - Ívar Örn Benediktsson 1978- (2009)
Ritgerðin samanstendur af fjórum ritrýndum greinum og samantekt. The present thesis describes the end moraines and ice-marginal processes of two surge-type glaciers in Iceland, Brúarjökull and Eyjabakkajökull. The aim of the research was to increase current understanding of fast flowing ice, and to identify causal links between glaciotectonics and glaciodynamics. The results show that a mosaic of coupled and decoupled spots existed under the glaciers during surges, leading to variations in ice-flow mechanism and ice-marginal formations. At Brúarjökull, decoupling at the sediment/bedrock interface was the dominating mechanism behind the rapid ice-flow. This resulted in downglacier dislocation of the sediment and the formation of marginal sediment wedges on which proglacial, single-crested, and fold-dominated moraines formed instantaneously on the last day of the surge. Where deformation of the bed contributed most to the increased ice flow, the end moraines formed by thrusting in the submarginal zone. The end moraines at Eyjabakkajökull are characterised by lateral variability in morphology and internal architecture. Large moraines with multiple symmetric crests are composed of overturned and overthrusted anticlines, while moraines with multiple asymmetric crests indicate imbricate thrust sheets. Both types of moraines formed where the foreland wedge was thick and the subglacial ice-flow mechanism was most likely dominated by deformation of the bed. In contrast, small, single-crested moraines formed in relation to sediment/bedrock decoupling where the foreland wedge was thin. The time frame for the formation of the end moraines was two to six days. This study implies that surge end moraines are integrally related to the mechanism of ice flow. Future studies should, therefore, not only focus on the internal architecture of the moraines but also on the subglacial bed for relating their structural evolution to the glacier dynamics. Such an approach would increase current understanding of the dynamics and marginal ...